The Policy of Banning Imports of Used Clothing to Protect Consumers as an Manifestation of the Principles of a Welfare State - Raudhea Vara Yulfa Chairy (Journal of Creative Power and Ambition (JCPA), 2026)
The government has enacted a policy banning the import of used clothing, based on Law Number 7 of 2014, specifically Articles 111 and 112. This policy was followed by other technical regulations in Government Regulations, Ministerial Regulations, and Ministerial Decrees. This policy is intended to protect MSMEs in terms of business competition. The legal issue that then arose was that the government had enforced the law repressively in Indonesia, in taking action against those involved in the sale of used clothing, even though the preamble to the 1945 Constitution requires the state to ensure that the livelihood of many people is the creation of general welfare. The research method used in this research is socio-legal, which examines the law by contesting existing social facts, with a descriptive analytical nature and data collection carried out primarily in the form of interviews, observations and documentation of related legal documents. The results of this study conclude that the policy of banning imported clothing is ineffective in curbing the flow of illegal imported clothing shipments due to several factors: First, the quantity of human resources available for law enforcement. Second, the scarcity of jobs causes local residents to continue selling illegal imported clothing. Third, alternatives that are not repressive but persuasive, along with proportional law enforcement, are needed.